Respuesta :
A.)
x + 3y = 11
5x - y = 17 ⇒ 15x - 3y = 51
15x = 62
B.) x + 3y = 11
15x = 62
x + 3y = 11
5x - y = 17
x = 11 - 3y
5x - y = 17
5(11-3y) - y = 17
55 - 15y - y = 17
-16y = 17 - 55
-16y = -38
y = -38/-16
y = 2.375
x = 11 - 3y
x = 11 - 3(2.375)
x = 11 - 7.125
x = 3.875
x = 3.875 ; y = 2.375
x + 3y = 11
3.875 + 3(2.375) = 11
3.875 + 7.125 = 11
11 = 11
x + 3y = 11
5x - y = 17 ⇒ 15x - 3y = 51
15x = 62
B.) x + 3y = 11
15x = 62
x + 3y = 11
5x - y = 17
x = 11 - 3y
5x - y = 17
5(11-3y) - y = 17
55 - 15y - y = 17
-16y = 17 - 55
-16y = -38
y = -38/-16
y = 2.375
x = 11 - 3y
x = 11 - 3(2.375)
x = 11 - 7.125
x = 3.875
x = 3.875 ; y = 2.375
x + 3y = 11
3.875 + 3(2.375) = 11
3.875 + 7.125 = 11
11 = 11
Answer:
x=3.875, y=2.375
Step-by-step explanation:
The system we are given is:
[tex]\left \{ {{x+3y=11} \atop {5x-y=17}} \right.[/tex]
We will use elimination to solve this. We will make the coefficients of y the same by multiplying the bottom equation by 3:
[tex]\left \{ {{x+3y=11} \atop {3(5x-y=17)}} \right. \\\\\left \{ {{x+3y=11} \atop {15x-3y=51}} \right.[/tex]
Since the coefficients of y are the same with different signs, we will add the equations to eliminate y:
[tex]\left \{ {{x+3y=11} \atop {+(15x-3y=51)}} \right. \\\\16x=62[/tex]
Divide both sides by 16:
16x/16 = 62/16
x = 3.875
Now we substitute this in place of x:
3.875+3y = 11
Subtract 3.875 from each side:
3.875+3y-3.875 = 11-3.875
3y = 7.125
Divide both sides by 3:
3y/3 = 7.125/3
y = 2.375